2007
DOI: 10.1292/jvms.69.1187
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous Nephritis and Meningoencephalomyelitis Caused by Halicephalobus gingivalis in a Pony Gelding

Abstract: ABSTRACT. A ten-year-old Shetland pony gelding showed low appetite, ataxia, peculiar swaying, clouding of consciousness, and ultimately died. At necropsy, multiple coalescing granulomatous foci were detected in the kidneys, and small necrotic lesions were found in the cerebellum. Histologic examination of the renal tissue sections revealed extensive granuloma, and Halicephalobus gingivalis-like nematodes were seen. Similar nematodes were found in the granulomatous or necrotic lesions of the renal lymph nodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 14 publications
4
28
0
Order By: Relevance
“…Infection may be restricted to local lesions or involve multiple organs through the hematogenous and lymphatic spread of the parasite [7, 9]. The most affected organs are brain, kidney, oral and nasal cavities, spinal cord, eye and lymph nodes [1, 7, 916].…”
Section: Introductionmentioning
confidence: 99%
“…Infection may be restricted to local lesions or involve multiple organs through the hematogenous and lymphatic spread of the parasite [7, 9]. The most affected organs are brain, kidney, oral and nasal cavities, spinal cord, eye and lymph nodes [1, 7, 916].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, nematodes most likely invade the bloodstream and lymphatic system and thus reach different organs (e.g. kidneys, liver and brain) where the number of nematodes increases rapidly through parthenogenetic reproduction (Akagami et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Four cases in horses have been reported so far in Italy, all native animals which apparently had never left the country, confirming the presence of the parasite in Italy (Cantile et al, 1997;Mandrioli et al, 2002). Worldwide, only three humans cases with fatal outcome have been reported, in all of which the CNS was involved (Akagami et al, 2007;Gardiner et al, 1981;Shadduck et al, 1979), but no human case has been reported in Italy so far. Borna disease was diagnosed in 2 sheep.…”
Section: Discussionmentioning
confidence: 99%